2021
DOI: 10.1016/j.jvsv.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of acute lower extremity deep venous thrombosis diagnosed by duplex in patients hospitalized for coronavirus disease 2019

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 23 publications
2
66
0
3
Order By: Relevance
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 observational studies included, four were prospective 9 29 30 31 and the remaining 30 were cross-sectional and retrospective studies. 7 11 30 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 All studies enrolled hospitalized patients with confirmed diagnosis of COVID-19; 11 focused on intensive care unit (ICU) population. 7 29 30 38 40 42 48 50 51 52 53 The total numbers of studies reporting the incidence of VTE or bleeding in patients receiving no prophylaxis, standard-dose prophylaxis, intermediate-dose prophylaxis, and therapeutic-dose anticoagulants were 7, 32, 8, and 13, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled incidence of total VTE according to the pharmacologic thromboprophylaxis received were as follows: no prophylaxis 41 . Pair-wise comparison revealed a significant difference between no prophylaxis versus standard-dose prophylaxis (p ¼ 0.007), no prophylaxis versus intermediate-dose prophylaxis (p ¼ 0.009), and no prophylaxis versus therapeutic-dose anticoagulants (p ¼ 0.002).…”
Section: Pharmacologic Thromboprophylaxis Strategies and Incidence Ofmentioning
confidence: 99%
“…6,9 Multiple reports of venous thromboembolism (VTE), arterial thrombosis, acute stroke, clotting of vascular access catheters and dialysis circuits have been described in Covid-19 patients. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Per published reports, the cumulative incidence of VTE (deep venous thrombosis and pulmonary embolism) in Covid-19 patients varies from 7.7% up to 69%. [10][11][12][16][17][18][19][20][21][22][23][24][25][26][27] The pathophysiology of CAC includes 2 mechanisms: systemic inflammation or cytokine storm causing endothelial cell activation and injury in the lung micro vasculature leading to pulmonary micro thrombosis and a hypercoagulable state leading to large vessel thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“… 29 The true prevalence of thromboembolic complications in ICU patients with Covid-19 is difficult to estimate, as it may not be feasible to transport critically ill patients and there is a risk of nosocomial spread of the virus among healthcare staff and hospitalized patients, thereby limiting diagnostic imaging studies. 14 It is also unclear if patients with Covid-19 associated coagulopathy are prone to develop thrombotic events with time and if thrombotic events are associated with higher mortality. The primary aim of our study was to prospectively investigate the cumulative incidence of thromboembolic events in hospitalized Covid-19 patients needing ICU admission and assessing the utility of point of care ultrasound (POCUS) to screen and diagnose lower extremity deep venous thrombosis (DVT).…”
Section: Introductionmentioning
confidence: 99%